2007
DOI: 10.1123/japa.15.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Exercise in Elderly Men and Women: Findings from the Swedish National Study on Aging and Care

Abstract: This study investigated the relationship between light and strenuous exercise and depression, as well as gender differences in this relationship, in a representative sample of 860 elderly Swedish suburb-dwelling men and women in age cohorts from 60 to 96 years, drawn from among participants in the Swedish National Aging and Care study. The relationship between depression and self-reported changes in exercise status over time was also examined. Exercise activities were measured with four survey questions, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 40 publications
4
48
1
4
Order By: Relevance
“…An exercise intervention study found that strenuous exercise had a significant effect on reducing depression in Swedish older men but not women (n=860) aged 60-89 but that light activity one had a significant effect on depression for women [48]. Studies analyzing the effects of different domains and activity may also explain this relationship.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…An exercise intervention study found that strenuous exercise had a significant effect on reducing depression in Swedish older men but not women (n=860) aged 60-89 but that light activity one had a significant effect on depression for women [48]. Studies analyzing the effects of different domains and activity may also explain this relationship.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…As respostas ao treino de endurance e força, por indivíduos idosos, mantêm e melhoram os níveis de volume de oxigénio (VO 2 ) máximo, débito cardíaco e diferença arterio--venosa de O2, ajudando a compensar a redução na massa e força muscular tipicamente associada ao processo de envelhecimento. (Oliveira, 2005;WHO, 2006;Edwards & Tsouros, 2006;Bennett et al, 2006;Lindwall et al, 2006;WHO, 2007a;Nelson et al, 2007).…”
Section: A Act Ividade Física Em Program As De Prom Oção Da Saúdeunclassified
“…Growth curve models revealed that all groups exhibited statistically and clinically significant reductions on HAM-D and BDI scores. However, patients which were receiving medication alone exhibited the fastest initial response; among patients receiving combination therapy, those with less severe depressive symptoms initially showed a more rapid response than those with initially more severe depressive symptoms (Lindwall, Rennemark, Halling, Berglund, & Hassmen, 2007).…”
Section: Phq-9 Score ≤4 (No Depression)mentioning
confidence: 99%